Development prospects of youth-friendly clinics under healthcare reform - Yuliia Matvieieva; Salvin Paul; Tetiana Honchar (Health Economics and Management Review)
This article analyzes the preconditions for «youth-friendly» services development. The study aims to justify the development prospects and identify ways to improve the efficiency of the Center for Health and Social Assistance to Children and Youth «Youth-Friendly Clinic» in Shostka under healthcare reform. The object of the study is the Center for Health and Social Assistance to Children and Youth «Youth-Friendly Clinic». The study's subject is the organizational, economic and social relations that arise of the Center for Health and Social Assistance to Children and Youth «Youth-Friendly Clinic» under healthcare reform. The methodological basis of this study is a systematic approach and fundamental premises of the general economic theory. The study involved scientific research methods such as abstract-logical and system-structural analysis to determine the problems leading to the need for «youth-friendly» services; statistical and expert assessments methods to determine the number of visits to the «Youth-Friendly Clinic». The research involved data for 2017-2019. The study determined several global problems that caused the emergence and development of youth-friendly clinics as follows: the risk of morbidity of young people through an active lifestyle; low awareness of young people about the importance of maintaining their own health; lack of specialists competent in socio-psychological problems of today's youth. Besides, the findings showed that the main prerequisite for youth-friendly clinic development is achieving sustainable development goals, especially goal 3 «Good health and well-being». This study considered preventive work, voluntary counselling and testing for HIV (VCT), medical-diagnostic and social areas of the Center for Health and Social Assistance to Children and Youth «Youth-Friendly Clinic» in Shostka. The authors analyzed the visit dynamic and the share of specialists in-demand among clients of the Center. The most active groups of clients were identified by age and sex. The obtained results allowed identifying the effective management tools of the researched Center, prospects and ways to improve its activity under healthcare reform. The authors indicated further research directions considering the impact of the COVID-19 pandemic on the youth-friendly clinics and the best world practice in the youth clinics management system.